Palmoplantar Pustulosis and Allergies: A Systematic Review - Alexandra M.G. Brunasso Vernetti; Matteo Puntoni; Cesare Massone (Mattioli1885, 2019)
Background: In 2007 the International Psoriasis Council considered palmoplantar pustulosis (PPP) a condition separate from psoriasis, and several authors maintain that PPP is a reactive process to metal contact allergies independent from psoriasis. Objectives: To evaluate the frequency of allergies and psoriasis in patients with PPP and to determine the role of allergens in PPP. Methods: A systematic search of the English databases (PubMed and Web of Science) from January 1964 to August 2018 to identify all patients affected by PPP and allergies and/or psoriasis. Results: In total, 16 publications describing a total of 519 patients with PPP were evaluated and 122 cases of concomitant PPP and metal allergy were found. The frequency of allergies among patients with PPP was 22.7%; between the identified allergens, 84.3% of cases correspond to metal allergies. In 65.1% of metal allergies, an improvement in PPP was seen after withdrawal of contact. The concomitant presence of psoriasis was recorded in 18% of the cases. Conclusion: There is some evidence to support the association of PPP with metal allergies but also with psoriasis, suggesting the role of metal allergens as a trigger factor in patients with PPP.